Analysing Trends in the Imprisonment of Women in Australia and New Zealand. Issue 2 (3rd March 2016) - Jeffries, Samantha; Newbold, Greg
Abstract : As in the United States and many other Western nations, incarceration rates in Australia and New Zealand have risen significantly over the past two decades. An interesting aspect of this trend is that internationally, incarceration rates for females have increased faster than those for men. A number of researchers in the United States and the United Kingdom have attempted to explain this phenomenon. This article looks at two countries that are culturally similar and geographically close: Australia and New Zealand. Disproportionate rises in female prison populations are visible in these jurisdictions. Focussing on the 2001–2012 period, the reasons for the disproportionate rises in female incarceration rates are hypothesized and compared. It is suggested that while the drivers of the changes are in some cases similar, there are also some interesting differences between the two countries.